Alterations in intracellular deoxyribonucleotide levels of mutationally altered ribonucleotide reductases in Escherichia coli. - Platz, A (1985)
Four recombinant plasmid clones (pPS305, pPS308, pPS317, and pPS319) coding for Escherichia coli ribonucleotide reductase have been characterized in vivo and in vitro. Each clone carried a different missense mutation affecting the B1 subunit. Measurements were made of deoxyribonucleoside triphosphate pools. Cells carrying the wild-type plasmid, pPS2, overproduced ribonucleotide reductase 10 to 20 times. As a consequence of this elevated enzyme level, the deoxyribonucleotide pools were approximately three times higher. All four mutant clones showed disturbed deoxyribonucleotide pools. The in vitro studies involved chromatography on affinity media, measurements of enzyme activity and allosteric regulation with a variety of substrates and effector molecules, and direct photoaffinity labeling in the presence of dTTP. Clones pPS305 and pPS308 were shown to code for catalytically defective enzymes, whereas clones pPS317 and pPS319 were shown to code for allosterically altered enzymes. The characterized missense mutations can thus be localized to areas involved in regulation of the substrate specificity or to the active site of protein B1. The alteration of the deoxyribonucleotide pools found in cells containing the allosterically defective clones pPS317 and pPS319 clearly demonstrated in vivo significance for the allosteric control of protein B1 in E. coli cells.